2017
DOI: 10.1111/pbi.12733
|View full text |Cite
|
Sign up to set email alerts
|

Engineering canker‐resistant plants through CRISPR/Cas9‐targeted editing of the susceptibility gene CsLOB1 promoter in citrus

Abstract: SummaryCitrus canker, caused by Xanthomonas citri subsp. citri (Xcc), is severely damaging to the global citrus industry. Targeted editing of host disease‐susceptibility genes represents an interesting and potentially durable alternative in plant breeding for resistance. Here, we report improvement of citrus canker resistance through CRISPR/Cas9‐targeted modification of the susceptibility gene CsLOB1 promoter in citrus. Wanjincheng orange (Citrus sinensis Osbeck) harbours at least three copies of the CsLOB1 G … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
343
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 601 publications
(350 citation statements)
references
References 48 publications
3
343
0
4
Order By: Relevance
“…Here, we employed the CaMV 35S promoter and the Yao promoter to drive LbCas12a expression (Figure b and c). However, in transgenic citrus, both CaMV 35S and AtU6‐1 were successfully used to drive sgRNAs for CRISPR‐SpCas9 (Jia et al ., ; Peng et al ., ) and for CRISPR‐SaCas9 (Jia et al ., ). To guarantee that the crRNA could be efficiently expressed in LbCas12a‐crRNA‐lobp‐transformed citrus, both CaMV 35S and AtU6‐1 were employed to drive crRNA (Figure b and c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we employed the CaMV 35S promoter and the Yao promoter to drive LbCas12a expression (Figure b and c). However, in transgenic citrus, both CaMV 35S and AtU6‐1 were successfully used to drive sgRNAs for CRISPR‐SpCas9 (Jia et al ., ; Peng et al ., ) and for CRISPR‐SaCas9 (Jia et al ., ). To guarantee that the crRNA could be efficiently expressed in LbCas12a‐crRNA‐lobp‐transformed citrus, both CaMV 35S and AtU6‐1 were employed to drive crRNA (Figure b and c).…”
Section: Resultsmentioning
confidence: 99%
“…The longer deletions could be attributable to 5′ overhangs resulting from the stagger cutting of Cas12a at sites distal to the PAM (Tang et al ., ; Zetsche et al ., ). Interestingly, all of the Type II CsLOBP mutations generated by LbCas12a were 1 bp deletions among the colonies that were sequenced (Figure b and c, Figure S2A), and they are similar to the short indels (1–2 bp) induced by SpCas9 in citrus (Jia et al ., , ; Peng et al ., ; Zhang et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The number and type of LOB1 alleles differ among citrus genomes. For instance, Duncan grapefruit has two allele types in a ratio 1:1 [87] and Wanjincheng orange has two in a ratio 3:1 [88], whereas Satsuma mandarin and Chandler pummelo harbor only one [89,90].…”
Section: Secretion Systems and Effectorsmentioning
confidence: 99%
“…Since grapefruit resulted from hybridization between sweet orange and pummelo (C. maxima) [139], it contains CsLOB1 alleles from both sweet orange (type I) and pummelo (type II). Later, Peng et al [88] showed that Cas9/ sgRNA-mediated editing of the EBEs of both CsLOB1 alleles in Wanjincheng orange (C. sinensis) conferred high levels of resistance against CCK. Reduced susceptibility was also obtained when the coding sequence of CsLOB1 in Duncan grapefruit was edited using Cas9/sgRNA technology [140].…”
Section: Plant Genetic Resistancementioning
confidence: 99%
“…Clustered regularly interspaced short palindromic repeat (CRISPR)/Cas9/single guide RNA (sgRNA) have been already successfully used to obtain genetically modified rice, wheat, Arabidopsis, tobacco and sorghum (Nekrasov et al, 2013;Shan et al, 2013). In citrus, genetic modification has been used either for general objectives like gene function detection (Jia and Wang, 2014) or for specific objectives as citrus canker resistance (Peng et al, 2017).…”
Section: Vi42 Genome Editingmentioning
confidence: 99%